Effect of Phase Change Material Heated by Solar Energy on the Flow Assurance of Heavy Crude Oil - Ghassan Al-Doori; Osama H. Al Naamani; Girma T. Chala (Tikrit Journal of Engineering Sciences)
As the world's energy demand rises, crude oil and other hydrocarbon resources are required for different sectors to fulfill the global energy demand. Heavy crude oils are often difficult to transport due to their high viscosity and low mobility. Oil companies employ techniques including mixing, heating, and injection to lessen the viscosity of crude oil, as well as nanotechnology to lessen the viscosity. The present study aims to gradually reduce the viscosity of heavy crude oil by heating it using solar energy as clean energy. Solar water heater, PCM paraffin wax, heat exchangers, crude oil, and other materials were used. In this study, wax was used to store solar energy during the day and release it at night after sunset. It was observed that as the temperature increased, the viscosity fell, and vice versa. For instance, when using heavy crude oil, the viscosity rose to 8 cP at 45°C and 3 rpm and fell to 3 cP at 81°C. The viscosity was 15 cP at 45°C and 6 rpm and 4 cP at 81°C. A novel phase change material, such as wax and sand. In general, it is recommended to use solar energy systems integrated with latent thermal storage, i.e., phase change materials (organic), e.g., wax, and (inorganic), e.g., salts, or sensibly use non-phase change materials, e.g., sand ensure the provision to provide the necessary heat, to liquefy the oil (reduce viscosity), for facilitating its continuous flow through pipelines, without affecting the environment.